2015
DOI: 10.1002/ijc.29893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subclasses of hepatocellular carcinoma predict sensitivity to fibroblast growth factor receptor inhibition

Abstract: A recent gene expression classification of hepatocellular carcinoma (HCC) includes a poor survival subclass termed S2 representing about one third of all HCC in clinical series. S2 cells express E-cadherin, and c-myc and secrete AFP. As the expression of fibroblast growth factor receptors (FGFRs) differs between S2 and non-S2 HCC, this study investigated whether molecular subclasses of HCC predict sensitivity to FGFR inhibition. S2 cell lines were significantly more sensitive (p<0.001) to the FGFR inhibitors B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Increasing evidence suggests that activation of FGF signaling pathways in HCC contributes to its malignancy . Therefore, we examined the antiproliferative activity of lenvatinib against nine HCC cell lines, and we showed that lenvatinib has inhibitory activity against HCC cell lines with activated FGF signaling pathways ; this proliferation inhibition was accompanied by suppressed FRS2 phosphorylation (Figs and ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Increasing evidence suggests that activation of FGF signaling pathways in HCC contributes to its malignancy . Therefore, we examined the antiproliferative activity of lenvatinib against nine HCC cell lines, and we showed that lenvatinib has inhibitory activity against HCC cell lines with activated FGF signaling pathways ; this proliferation inhibition was accompanied by suppressed FRS2 phosphorylation (Figs and ).…”
Section: Discussionmentioning
confidence: 91%
“…Activation of the FGF signaling pathways is associated with HCC progression, and proliferation of subsets of HCC is dependent on FGF signaling pathways . Because lenvatinib inhibits FGFRs, we first examined the antiproliferative activity of lenvatinib against nine HCC cell lines in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that FGFRs are presented on endothelial cells, and provide critical signaling pathways for HCC metastasis (Presta et al, 2005;Huynh et al, 2008). Schmidt et al (2016) revealed that the classification system may help identify HCC patients who are most likely to benefit FGFR inhibition. Furthermore, combined FGFR/mTOR treatment showed significant inhibitory effects on signaling and motility in HCC (Scheller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One early study showed that non-specific FGFR inhibitors quelled HCC cell growth and induced apoptosis [55] . It was later found that non-specific FGFR inhibitory compounds were particularly effective in HCC cells expressing FGFR4 and FGF19 [61] . Selective FGFR4 inhibitors have also been developed.…”
Section: Targeting the Fgf19-fgfr4/klb Axis For The Treatment Of Hccmentioning
confidence: 99%
“…Its stimulation either by treatment with FGF19 or overexpression of FGFR4, and its inhibition by knocking down FGF19, FGFR4 or KLB, or by the overexpression of dominant-negative FGFR4 variants, has been shown to impact on HCC cell proliferation, survival, epithelial-mesenchymal transition (EMT), migration and invasion [33,37,38,49,50,55,58,60,61] . Interestingly, FGF19 may amplify its biological effects on HCC [62] and the EGFR ligand amphiregulin (AREG) in HCC cells, and that the growth-stimulating effects of FGF19 were mediated in part by autocrine AREG production [33] .…”
Section: Defining a Role For The Fgf19-fgfr4/klb Signaling System In mentioning
confidence: 99%